INSPECTION AND MODERNIZATION OF WORKING BODIES TOOL FOR SURFACE TREATMENT OF SOIL - KutkovetskaТ. О. (Systems and Technologies, 2026)
The article conducts theoretical and practical research on the existing working bodies of tools for surface tillage and proposes their modernization in order to improve the quality of tillage and reduce energy consumption for performing technological operations. As a result of the research we conducted, we found that there are different designs of working parts of machines and tools for surface tillage, such as arrow-shaped tines and discs, which are passive working parts and have a number of disadvantages, namely, soil sticking, incomplete cutting of weeds, etc. In addition, they do not fully meet the agrotechnical requirements for performing this type of work. The best performance is achieved by annular working bodies with passive and active drives. According to the results of the research, it was determined that for stable performance of surface tillage without soil clogging of the working elements and better destruction of weeds, their design should be in the form of rotary working elements with an active drive. A modernization of the working elements is proposed, which consists in their having the form of ring working elements with the division of the continuous cutting blade into separate parts and their rotation at an angle to the axis of rotation. Research has shown that the proposed working bodies of tools for surface tillage practically do not clog in this form and do not leave any defects. The advantage of this technical solution is that, in addition to all of the above, the proposed design of the working elements reduces their traction resistance and they completely cut the weeds. It has been determined that a promising direction in the development of soil cultivation equipment is the use of machines and tools equipped with rotary working bodies with an active drive to improve the quality of surface tillage, which meets the established agrotechnical requirements.